Wet-milling of waxy wheat flours and characteristics of waxy wheat starch - Guan, Lan (Kansas State University, 2008)
Waxy wheat starch contains almost all amylopectin and is relatively new. Currently, advanced lines of hard winter waxy wheats are being bred through genetic elimination of waxy proteins. To realize the full potential of waxy wheat, the wet-milling of waxy wheat flour to produce gluten and waxy wheat starch was investigated. Flours of six advanced lines of waxy hard wheats and two normal hard wheats cultivars, Karl '92 and Trego, were fractioned by the dough-washing method. Doughs prepared from the waxy flours were found to be weaker than those of from normal wheats. All the waxy wheat and normal wheat flours were wet-milled by the dough-washing (Martin) process and the yield and recovery of starch and gluten were compared. One waxy wheat flour, NWX02Y2459, was sticky during the early stages of dough washing, and it gave relatively poor gluten and starch recoveries with low purity. By mixing the dough with 2% NaCl solution or by adding hemicellulase, the stickiness of the dough subsided during the washing step, and thereby recoveries of the gluten and starch fractions were improved. Waxy wheat starch offers unique functional properties. Waxy wheat starches gelatinize and cook at a relatively low temperature compared to maize starches, and their pastes retrograde more slowly and to a lower extent than waxy maize starch. Pasting curves showed that waxy wheat starch generated a much higher viscosity at a lower temperature, and a lower setback viscosity than normal wheat starch and waxy maize starch. Changes in the morphology of waxy and normal wheat starch granules were determined by using a hot-stage microscope, and those changes were related to their pasting properties. After waxy wheat starch was cross-linked in an aqueous slurry at about 37% starch solids with 0.01% phosphoryl chloride (starch basis), visco-amylograms showed that viscosity breakdown was eliminated and that the cooked paste became non-cohesive (less "stringy"). Increasing levels of phosphoryl chloride at 0.03% and 0.06% caused a steady decline in the peak and final paste consistencies of cross-linked waxy wheat starch, whereas the consistencies of waxy maize starch proceeded through an optimum. Waxy maize starch cross-linked with 0.03% phosphoryl chloride had a higher peak and final consistency at 7% solids than when cross-linked with 0.01% and 0.06% phosphoryl chloride.
Keywords: Dry-milling; Waxy Wheat; Starch; Chemistry, Agricultural (0749)